Feasibility to Perform T2* Mapping Postcontrast Administration in Reperfused STEMI Patients for the Detection of Intramyocardial Hemorrhage. Issue 2 (14th May 2019) - Bulluck, Heerajnarain; Chowdhury, Nazia; Lim, Mei Xing; Allen, John C.; Bryant, Jennifer A.; Chan, Mark Y.; Chan, Mervyn H.H.; Chin, Calvin W.L.; Ho, Hee Hwa; Lim, Soo T.; Tan, Ru‐San; Tan, Jack W.; et al.
Abstract : Level of Evidence: 1 Technical Efficacy: Stage 2